THE USE OF FILM CLIPS AND VIDEO MEDIA WITH SUBTITLES IN ENGLISH VOCABULARY INSTRUCTION - Mulyani Mulyani; Salwa Chaira (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to provide an alternative of vocabulary teaching through the use of English-language film clips and videos with subtitles with relevant activities which was conducted towards students of Class XI of SMAIT Al Fityan School. This research was conducted online using one pretest and posttest group through a mixed method approach; qualitative and quantitative research (quasi experiment). The data in quantitative form come from online tests. The data in qualitative form, to clarify the test results, come from the questionnaires, interviews, and observations. Based on the nonparametric statistical tests taken by 30 students of Class XI IPA and XI IPS using the Wilcoxon Test with the value of Sig. or the P value 0.000 in which 0.000> α 0.05. This result shows a significant difference between the pretest and posttest. These results indicate that the use of clip film and video media with subtitles may support students’ understanding & improvement of vocabulary learning besides may obtain new learning experiences for the senior high school students.